The relation of group dynamics with the effectiveness of a team in an organization - Ramayanti, Nur Endah; Noor, Lorine Kalista; Rahmasita, Azi Nur; Pribadi, M. Iqbal (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2023)
The group dynamic is crucial for organizations in a highly competitive business environment. It signifies that each member successfully contributes to the shared goal. But, explaining in a group requires a separate point of view in order to comprehend what is going on and to focus on many people, each with their own unique perspective and response to the activity that was taking place. The purpose of this study is to examine the relationship between group dynamics with the team effectiveness in the organization. This study uses various perspectives from the previous literature until the present relating group dynamics and team effectiveness. This study provides general information about the studies on group dynamics and team effectiveness in organizations